Two‐dimensional Metal‐organic Frameworks for Electrochemical CO2 Reduction Reaction. Issue 3 (18th December 2021) - Zhan, Tingting; Zou, Yingbing; Yang, Ying; Ma, Xiuling; Zhang, Zhangjing; Xiang, Shengchang
Abstract: To lower CO2 emissions and address the current energy crisis, one of the most promising approaches that converting the captured CO2 into valuable chemicals and fuels via electrocatalysis is proposed recently. Metal‐organic frameworks (MOFs) as an emerging multifunctional material have been extensively designed for electrocatalytic reduction of CO2 . In terms of chemical and structural properties, 2D MOFs have obvious superiority over 3D bulk MOFs. Specifically, the large porosity and ultrathin structure of the 2D materials contribute to exotic properties such as enhanced electrical conductivity and rapid mass transport during reactions, which are in favor of electrocatalysis. In this review, the design strategies of 2D MOFs are discussed. Then, the recent advances of MOFs and their derivative catalysts with unique 2D structures for CO2 reduction are introduced. These examples are expected to provide clues to rational design strategies and synthesis of high‐performance CO2 electroreduction, beyond the bulk MOFs. Abstract : This review summarized the design strategies (surface engineering or molecular engineering) and application of 2D MOFs and their derived single‐atom catalysts in electrocatalytic CO2 reduction. The developed 2D MOFs catalysts were mainly constructed with the ligands containing macrocyclic conjugation (porphyrin, phthalocyanine, and others). The aim of this review is to provide an insight into 2D MOFs for the rational design of high‐performance electrocatalysts for CO2 reduction.